Impacted maxillary permanent first molar - Faisal Khalid Altalhi; Abdullah A. Alzamil; Bandar S. Shukr; Abdulaziz A. Alharbi; Ahmed S. Kowsar (Wolters Kluwer Medknow Publications, 2024)
Tooth impaction is an abnormality that occurs when a tooth does not emerge into its place in the dental arch. Impacted permanent molar is an unusual condition that is usually detected during a routine examination. This impaction type is mostly problematic and can cause serious issues, especially when early detection and appropriate treatment are not achieved. This article highlights a case with a complaint of an ill-fitting denture, accompanied by an impacted molar that was identified during routine radiographic examination. The available treatment options include periodic follow-up, surgical exposure and orthodontic repositioning, and more invasively, surgical extraction and prosthetic replacement. The case was treated by a nonsurgical prosthodontics approach, in addition to regular follow-up, avoiding surgical interventions. This approach successfully restored both the patient's function and esthetics. The case demonstrated the potential of prosthodontics therapy for managing impacted teeth and offering a minimally invasive and short treatment alternative to surgical and orthodontic interventions.